Markets and Firms: Notes toward the Future of Economic Sociology - Harrison C. White (Journal of Economic Sociology, 2010)
The paper suggests to analyze the production markets as social constructions. The author criticizes the stylized version of the pure competition. In any market every production firm learns to find its own special niche, which is different in the production volumes and the production quality from their rivals.  The decisions are taken on the basis of the rivals’ actions which are taken as the market signals. The markets reproduce themselves as molecules, formed by the atoms – production firms. Moreover is molecule has linear ordered atoms. Ordered niches comprise markets in the flows of intermediate products. The overall system and signal mechanism is described with the help of mathematic models. Next the author shows the main results which could be received with the help of equilibrium model and its impacts from the initial way.  The paper ends by the analysis of the possible changes of orientations in the flow and its evolution in time.